Pelaksanaan Rekrutmen Karyawan Pada CV. Cahaya Kartika Raya Tangerang Selatan Dengan Metode BSC - Luthfi Febri Indaryanto (International Forum of Researchers and Lecturers, 2023)
Currently the level of competition in every company is very tight, this also encourages competition in managing human resources, especially in recruiting and selecting employees. Cahaya Katika Raya Tangerang Selatan This shows that recruitment and selection play an important role in influencing the performance of a company's employees. The implication of this research study is that the company can pay close attention to and evaluate the recruitment and selection applied by the company in order to meet the company's human resource needs.